Energy, exergy, and economic evaluation of integrated waste incineration facility with a thermal power plant - Farid Aghapour sabagh; Siamak Hossainpour; Shayan Pourhemmati (Energy Conversion and Management: X, 2023)
Increased waste production and poor waste management have created severe negative environmental impacts. Waste incineration is a way to produce energy and decreases environmental impacts; however, this technique cannot be considered independently as a source of power generation because of its low performance. This study aims to evaluate the integration of a waste incineration system with a natural gas-fired power plant in terms of energy, exergy, and economic points. As a result of the proposed configurations, in addition to promoting efficiency and net power production, some equipment is removed from power plants. Efforts are made to increase the accuracy of simulation results by paying attention to the combustion process in boilers and predicting the actual working condition of feed water heaters. Results showed that the hybrid scheme improves electricity generation by up to 2.87 MW and boosts energy, and exergy efficiency by up to 0.32%, and 0.3%, respectively.